DNA Damage Response and Inflammatory Signaling Limit the MLL-ENL-Induced Leukemogenesis In Vivo - Takacova, Sylvia; Slany, Robert; Bartkova, Jirina; Stranecky, Viktor; Dolezel, Petr; Luzna, Pavla; Bartek, Jiri; Divoky, Vladimir (Cancer Cell, 2012)
Activation of the MLL-ENL-ERtm oncogene initiates aberrant proliferation of myeloid progenitors. Here, we show induction of a fail-safe mechanism mediated by the DNA damage response (DDR) machinery that results in activation of the ATR/ATM-Chk1/Chk2-p53/p21 checkpoint and cellular senescence at early stages of cellular transformation caused by a regulatable MLL-ENL-ERtm in mice. Furthermore, we identified the transcription program underlying this intrinsic anticancer barrier, and DDR-induced inflammatory regulators that fine-tune the signaling toward senescence, thereby modulating the fate of MLL-ENL-immortalized cells in a tissue-environment-dependent manner. Our results indicate that DDR is a rate-limiting event for acquisition of stem cell-like properties in MLL-ENL-ERtm-mediated transformation, as experimental inhibition of the barrier accelerated the transition to immature cell states and acute leukemia development. © 2012 Elsevier Inc.